Pemberdayaan Aparatur Gampong dalam Penyusunan Qanun Tentang Pencegahan Kekerasan Seksual di Gampong Uteun Kot Kota Lhokseumawe - Nirzalin Nirzalin; Suadi Suadi; Budi Bahreisy; Rizki Yunanda; Fakhrurrazi Fakhrurrazi; Richa Meliza; Kurniadi Kurniadi; Rauzana Hilda (Universitas Teuku Umar, 2025)
The availability of the Qanun on the Prevention of Sexual Violence represents a strategic and systematic step to address the issue of rampant adultery and sexual violence, particularly in Uteun Kot Village, Lhokseumawe City. As a village inhabited by residents with diverse cultural backgrounds due to the heterogeneity of its population, Uteun Kot is highly vulnerable to acts of adultery and sexual violence. The main problem addressed in this community service activity is how to formulate a village-level qanun on the prevention of sexual harassment as an effort to empower village officials. The method used in this activity is a quantitative approach, consisting of several stages: identifying cases of sexual violence, examining the prevention and resolution processes that have previously been implemented, and conducting training on drafting the Qanun for the prevention of sexual violence. The absence of such a qanun has placed village authorities in a position where they are unable to fully resolve family conflicts related to sexual violence. More importantly, preventive measures are not carried out in a planned, systematic, and measurable manner. This reality underscores the significance and urgency of establishing a qanun on the prevention of sexual violence in Uteun Kot Village. The presence of this qanun serves as a strategic solution for preventing and resolving conflicts rooted in sexual violence, thereby fostering and sustaining harmony within the community. Law enforcement, based on the qanun, guarantees the stability of social order by ensuring the existence of norms in community social practices. The qualitative outcome of this program is targeted to produce one Qanun on the Prevention of Sexual Violence for Uteun Kot Village. Furthermore, in terms of publication, the outputs include a scientific article published in a community service journal (OJS-based) and a media publication, both with published status